Numerical modelling of a female breast with and without tumour using thermographic measurements - Natteri M. Sudharsan (2008)
Breast cancer is a common and dreadful disease among women. Regular screening helps in its early detection. At present the most common methods of screening are self-examination and mammography. The surface temperature distribution of the breast can also provide some information on the presence of an underlying tumour. This distribution has a relation to the size and location of tumour and can be seen using thermography, where the infrared radiation emitted from the surface of the breast is recorded and a thermal pattern obtained. Thermography is a non-invasive and an inexpensive tool, which could be used for early detection. The aim is to develop not only a tool that is affordable, but also reliable in detecting breast cancer. It is hoped that the surface temperature pattern obtained using thermography along with numerical simulation will provide a reasonable idea about the size and location of the tumour.